ATF5-Mediated Mitochondrial Unfolded Protein Response (UPR mt ) Protects Neurons Against Oxygen-Glucose Deprivation and Cerebral Ischemia - An, Hong; Zhou, Bing; Hayakawa, Kazuhide; Durán Laforet, Violeta; Park, Ji-Hyun; Nakamura, Yoshihiko; Mandeville, Emiri T; Liu, Ning; Guo, Shuzhen; Yu, Zhanyang; Shi, Jingfei; Wu, Di; et al. (Stroke (1970), 2024)
The mitochondrial unfolded protein response (UPR ) is an evolutionarily conserved mitochondrial response that is critical for maintaining mitochondrial and energetic homeostasis under cellular stress after tissue injury and disease. Here, we ask whether UPR may be a potential therapeutic target for ischemic stroke. We performed the middle cerebral artery occlusion and oxygen-glucose deprivation models to mimic ischemic stroke in vivo and in vitro, respectively. Oligomycin and meclizine were used to trigger the UPR . We used 2,3,5-triphenyltetrazolium chloride staining, behavioral tests, and Nissl staining to evaluate cerebral injury in vivo. The Cell Counting Kit-8 assay and the Calcein AM Assay Kit were conducted to test cerebral injury in vitro. Inducing UPR with oligomycin protected neuronal cultures against oxygen-glucose deprivation. UPR could also be triggered with meclizine, and this Food and Drug Administration-approved drug also protected neurons against oxygen-glucose deprivation. Blocking UPR with siRNA against activating transcription factor 5 eliminated the neuroprotective effects of meclizine. In a mouse model of focal cerebral ischemia, pretreatment with meclizine was able to induce UPR in vivo, which reduced infarction and improved neurological outcomes. These findings suggest that the UPR is important in maintaining the survival of neurons facing ischemic/hypoxic stress. The UPR mechanism may provide a new therapeutic avenue for ischemic stroke.